1953
DOI: 10.1099/00221287-9-2-207
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Direct Viable Counts of the Facultatively Anaerobic Microflora in the Rumen of a Sheep maintained on a Hay Diet

Abstract: SUMMARY: By direct viable counts in deep cultures in a basal nutrient agar, consisting of buffered and very highly clarified nunen liquor, supplemented only with vitamin-free acid hydrolysate of casein, tryptophan, a fermentable carbohydrate and agar, the crude wet nunen contents of a hay-fed sheep has been shown to contain a population of c. lo8 viable and facultatively anaerobic bacteria per g., mostly Gram-positive cocci capable of fermenting'a wide range of soluble carbohydrates including starch and inulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1954
1954
1980
1980

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The scheme put forward by Moir & Masson would seem to afford a method of quantitative evaluation of a bacterial population through differential counts, and might provide a useful control in many studies of a biochemical nature. Heald, Krogh, Mann, Appleby, Masson & Oxford (35) have devised a direct method for making viable counts of facultative anaerobes, and have reached the conclusion that facultative anaerobes play a more important role in rumen metabolism than had been previously believed, this early lack in recognizing their importance being due to a concentration of attention on the strictly anaerobic process of cellulose digestion. Mann, Masson & Oxford (36), in a further study of the facultative anaerobes of the previous paper, have shown that of 120 streptococcal isolates 82% showed fermentation and other reactions similar to those of Streptococcus bovis, 6 % resembled Strep, faecalis and the rest (12%) were unclassifiable.…”
Section: Rumen Bacteriamentioning
confidence: 95%
“…The scheme put forward by Moir & Masson would seem to afford a method of quantitative evaluation of a bacterial population through differential counts, and might provide a useful control in many studies of a biochemical nature. Heald, Krogh, Mann, Appleby, Masson & Oxford (35) have devised a direct method for making viable counts of facultative anaerobes, and have reached the conclusion that facultative anaerobes play a more important role in rumen metabolism than had been previously believed, this early lack in recognizing their importance being due to a concentration of attention on the strictly anaerobic process of cellulose digestion. Mann, Masson & Oxford (36), in a further study of the facultative anaerobes of the previous paper, have shown that of 120 streptococcal isolates 82% showed fermentation and other reactions similar to those of Streptococcus bovis, 6 % resembled Strep, faecalis and the rest (12%) were unclassifiable.…”
Section: Rumen Bacteriamentioning
confidence: 95%
“…Anaerobiosis was obtained by flushing the container vessels with nitrogen in the manner described in that paper. Water/gel cultures were prepared in small screw-capped bottles according to the method of Heald, Krogh, Mann, Appleby, Masson & Oxford (1953), with the modification that the concentration of agar in the solid layer was only 0.5 yo. When this nutrient layer incorporating the inoculum had set, the bottle was carefully filled with freshly-boiled cold sterile water up to the rim and the cap screwed down.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent paper (Heald et al 1953) a method of counting viable saccharolytic bacteria from a sheep's rumen was described (hereinafter referred to as the 'bottle count ') in which the basal medium consisted of rumen liquor itself, suitably clarified and sterilized after withdrawal , from hay-fed sheep and supplemented by nothing more than a vitamin-free mixture of amino acids, a soluble fermentable carbohydrate and agar. In this way it was hoped that only bacteria genuinely active under rumen conditions would be counted.…”
mentioning
confidence: 99%
“…By picking off colonies from the agar-shake cultures, some 300 isolates were eventually obtained in pure culture representing, for the most part, small cocci and Gram-negative rods present in numbers exceeding lOO,OOO/g. wet rumen contents (see Table 2 in Heald et al 1953). Since the methods used ensured that only the active carbohydrate fermenters would grow, these isolated bacteria were regarded as of actual or potential importance in rumen fermentations.…”
mentioning
confidence: 99%